KEDUDUKAN PRIBUMI-PENDATANG DI PASAR DAN KANTOR: KONFLIK (HORIZONTAL) EKONOMI-POLITIK DI PAPUA - Kristofel Maikel Ajoi (Cakrawala Jurnal Penelitian Sosial, 2016)
The economic domination of outsiders in Papua very influential for their political action. Economic situation in Papua become significant of necessary as power instrument. The domination is fact to saw how they become high class community. While, the Papuan People only well of the second class community. The Motivation invaded of outsiders to Papua are about economic factors and mostly is political policy. Invaded outsiders, made empower of their powerful because equality of peoples in Papua ins’t equal and dominated by outsiders. So they used that potential natural resources for their economic existence. That’s is key problems of horizontal conflict between Indegenous Peoples of Papua with outsider (transmigrasi dan migrasi) in Papua. This research to describe how Papuan condition now and how condition in polical-economic in Papua become the dominant power of outsiders in order to domination. Research Approach and the research method is qualitative-verification to put more problems about domination and greavance that become key of horizontal conflict between indigenous People of Papua and outsiders in Papua. Mostly of the research saw matters and information from interview and discusses, and also used observation and the life history from researcher and most people from Papua. Key words: Horizontal conflict, political-economic, indigenous, outsiders